190k views
1 vote
Use the table below to answer this question:

x y
−3 −3
0 3
1 5
Find the average rate of change for the given function from x = −3 to x = 1.


2

−3

−1

−2

User AXM
by
6.2k points

2 Answers

2 votes

Answer:

A. 2

Explanation:

average rate of change from x1 to x2 is

[f(x2) - f(x1)]/(x2 - x1)

Here we have x1 = -3; f(x1) = -3; x2 = 1; f(x2) = 5

average rate of change from x1 to x2 =

= [f(x2) - f(x1)]/(x2 - x1)

= [5 - (-3)]/(1 - (-3))

= 8/4

= 2

User Laggel
by
5.9k points
5 votes

Answer:

2

Explanation:

We can find the average rate of change by using the formula

rate of change = (y2-y1) /(x2-x1)

= (5-3)/(1-0)

= 2/1

=2

User ABeanSits
by
5.3k points